Hacia una nueva relación entre el Perú y el Japón - Terada, Teresuke (2008)
Relations between Peru and Japan are introduced by Japanese Diplomat who frames inside of two vectors what Japanese politics considers: cooperation and multilateral exchange, insisting in those human bonds of that bilateral relation and the importance of Latin America to Japan’s economic and political condition. Finally, Fujimori case is briefly seen and a new period has started in the relations between Peru and Japan since the government of Alan Garcia.